Análises sobre a relação do uso de contraceptivos hormonais e padrão de sono em mulheres em idade fértil - Bezerra, Andréia Gomes [UNIFESP] (2019)
Female sexual hormones have known hypnogenic effects and the use of hormonal replacement therapy in postmenopausal women leads to improvement in sleep quality. However, the effects of hormonal contraceptives in premenopausal women is still scarcely understood. The present thesis consisted of two studies addressing the theme. The first one sought to evaluate the impact of hormonal contraceptive use on subjective sleep self-reports among premenopausal women through a web-based cross-sectional trial. A total of 2,055 premenopausal women between 18 and 40 years-old participated answering an online questionnaire evaluating hormonal contraceptive use, sleeprelated characteristics and related features. In addition to questions about the self-perception of sleep parameters, the sleep assessment tools comprised the Epworth Sleepiness Scale (ESS) and the Insomnia Severity Index (ISI). A first level of analysis assessed differences between hormonal contraceptive users and non-users. In a second level of analysis, we compared whether there was a significant difference in sleep parameters between combined contraceptive users and progestagen-only contraceptive users. Generations of contraceptives were evaluated at a third level of analysis and, finally, we assessed possible sleep effects between oral progestagen-only contraceptives and levonorgestrelreleasing intrauterine system type. Of the total sample, only 1286 participants met the inclusion criteria, of which 918 were using hormonal contraceptives (Combined: 848; Progestagen-only: 70). Hormonal contraceptive users reported more sleep complaints and higher scores on ESS and IGI, which means they had excessive daytime sleepiness and more insomnia symptoms. Women using progestagen-only contraceptives reported a shorter total sleep time compared to those using the combined contraceptive. Users of 3rd generation contraceptives presented lower total sleep time and higher IGI scores when compared with nonusers. Comparisons between users of levonorgestrel intrauterine devices and users of other progestagen-only hormonal contraceptives demonstrated a lower sleepiness score, as measured by ESS, among levonorgestrel intrauterine device users in both raw and corrected analysis (intrauterine device users: 9.12±4.57; other progestagens-only: 11.58±4.59). The second study addressed a systematic review and meta-analyses aiming at synthesizing the evidences about the effects of hormonal contraceptives in sleep among premenopausal women. The databases for the bibliographic research were Pubmed, Scopus and Web of Science. The Bibliographic search retrieved 2402 articles, which were reduced to a sample of ten articles after an articles selection process. In total 13 parameters related to sleep were meta-analyzed. It was only possible to include studies of before and after, transversal and cohort design. The only significant result was observed in the total time in the bed, however this data isolated from other sleep parameters does not allow robust conclusions. These data showed a lack of studies in this area and the need to promote research on the possible effects of hormonal contraceptives on sleep in women of reproductive age.